Modern concept of the etiology and pathogenesis of androgenetic alopecia - Ovcharenko , Yuliya; Salyenkova, Olena (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2021)
Introduction. The understanding of the etiology and pathogenesis of androgenetic alopecia (AGA) has formed modern therapeutic strategies for the treatment of this trichopathy. However, the significant prevalence of this pathology, limited therapeutic success, and differences in the response to standard therapy in male and female patients determine the interest in a more in-depth study and search for new links in the etiopathogenesis of AGA. Goal. Using a review of scientific publications in recent years on AGA in male and female patients, analyze and formulate the modern concept of the etiology and pathogenesis of this disease in order to further search for new treatment methods. Materials and methods. We searched and analyzed publications for the query «androgenetic alopecia, etiology, pathogenesis», the search was carried out using Google Scholar, considered articles that have been published since 2016. Results. The effect of androgens on hair follicles in androgen-dependent areas of the scalp under conditions of genetic predisposition is considered as the most studied and proven concept of AGA etiopathogenesis. However, recent studies have also revealed nonandrogenic cofactors, among which the pathological cascade of events «oxidative stress-microinflammation-fibrosis», which are determined at different stages of disease progression, is potentially interesting for further study. Knowledge of the phenomenon of apoptosis as an important factor in the disturbance of the dynamics of the hair cycle has been expanded. The management of perifollicular microinflammation and apoptosis can allow the control of the processes of sequential hair miniaturization and give a pronounced clinical result during the treatment of AGA. Thus, the nonandrogenic mechanisms of AGA pathobiology require further study. Conclusions. New data on the causes and mechanism of development of androgenetic alopecia in women and men have expanded our understanding of these processes. The need to supplement knowledge on this topic causes significant scientific interest and is very relevant, since they can be used to improve treatment for use in practical medicine.